1993
DOI: 10.1080/14640749308401089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exposure to a To-Be-Shocked Environment upon the Rat's Freezing Response: Evidence for Facilitation, Latent Inhibition, and Perceptual Learning

Abstract: Three experiments used the freezing response of rats to examine the effects of pre-exposure to an environment upon (1) its associability with shock and (2) its discriminability from a second environment. Experiments 1 and 2 demonstrated that freezing was proportional to the interval between exposure to the environment at time T1 and the occurrence of shock at T2. This function was shifted by pre-exposure to the to-be-shocked environment, with brief pre-exposures increasing (facilitation) and extended pre-expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
156
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(167 citation statements)
references
References 8 publications
10
156
1
Order By: Relevance
“…Moreover, there was also no evidence for an increased discrimination between the conditioning context and the second, novel context among saline-treated rats preexposed to the conditioning context. Both Kiernan and Westbrook (1993) and Westbrook et al (1997) provided evidence for such facilitation and increased discrimination among preexposed rats under similar conditions to those used here. Again, reason for this discrepancy is unclear but could be related to differences in the interval between conditioning and test (see Experiment 4).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Moreover, there was also no evidence for an increased discrimination between the conditioning context and the second, novel context among saline-treated rats preexposed to the conditioning context. Both Kiernan and Westbrook (1993) and Westbrook et al (1997) provided evidence for such facilitation and increased discrimination among preexposed rats under similar conditions to those used here. Again, reason for this discrepancy is unclear but could be related to differences in the interval between conditioning and test (see Experiment 4).…”
Section: Discussionsupporting
confidence: 66%
“…The rats remained there for a further 2 min after US delivery. We selected a 27-s placement-footshock interval (rather than the 120-s interval used previously) because work from our laboratories has shown that it is optimal for detecting an influence of context preexposure on context conditioning (e.g., Kiernan & Westbrook, 1993). We administered an unsignaled footshock (rather than the signaled footshock used previously) to show that the retrograde deficits induced by postconditioning exposures to morphine were independent of the use of a signaled footshock.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Substantial evidence from CFC studies indicates that a brief footshock with minimal time spent in a context produces poor retention of the training, an effect reversed by exposure to the context before the footshock (Fanselow 1986(Fanselow , 1990Kiernan and Westbrook 1993;Landeira-Fernandez et al 2006). Although the context and footshock are usually presented together, it is possible to present context and footshock training on separate days, allowing investigation of the separate mnemonic components of the task.…”
Section: Behavioral Trainingmentioning
confidence: 99%